(3QSGdI aj JMbjb GdhLhO GdPgfjs - (3eLghds
(3ChdgG (B:s
(3GYde Cf MGUd HQgGf GdJWHjb Cfg dh hLO LedI ZjQ eJfGgjI dhLO aj VefgG LedI CNQi ZjQ eJfGgjI CjVG dGf hLhO Gdcd jSJdRe hLhO GdLRA hdh hLO LedJGf ZjQ eJfGgjI aYfO GdJWHjb Gdeecfs
(3BNQgG (B:s
(3hGdaQb Hjf GdhLhO GdPgfj hGdCTHGM hGdCeKGd hMbjbJg LeYJ gPg GdJbQjQGJ ef GdehGba hTQMg hMGTjI TQM GdYbGjO GdYVOjI ddaGVd GdcdfhHj edNUG JCed aj gPG GdebGe EP bO Rd ajg CbOGe GdEYdGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs